Evaluation of Orifice Flow Meter Accuracy under Pulsation Conditions - Abdullah, mohammad; Idres, Moumen (Trans Tech Publications, Switzerland, 2015)
Orifice meter is a flow measuring device which is widely used in various industrial applications. Although the device gives accurate measurement during steady flow, measurement errors related to square root and sampling errors are unavoidable if pulsations exist. This research investigatesand improves the performance of an orifice plate flow meter under pulsation effects. A simple model for the pulsating flow through an orifice meter is presented. Square root error (SRE) is estimated. Sampling errors (SE) are reduced by proper selection of the averaging time